Website Development : How to Make a Simple Portfolio Website - Fajri, Muhammad Akbar Al; Azizah, Faza Shafa; Shidqi, Muhammad Abyan; Alfarizi, Muhammad Azis; Asyahri, Aldo Dwi; Adharani, Yana; Rosanti, Nurvelly; Mujiastuti, Rully; Jumail, Jumail (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2024)
Kegiatan webinar dan workshop